Kappa-carrageenan-Functionalization of octacalcium phosphate-coated titanium Discs enhances pre-osteoblast behavior and osteogenic differentiation - Cao, Wei; Jin, Jianfeng; Wu, Gang; Bravenboer, Nathalie; Helder, Marco N.; Schulten, Engelbert A. J. M.; Bacabac, Rommel G.; Pathak, Janak L.; Klein-Nulend, Jenneke (Frontiers in Bioengineering and Biotechnology, 2022)
Bioactive coatings are promising for improving osseointegration and the long-term success of titanium dental or orthopaedic implants. Biomimetic octacalcium phosphate (OCP) coating can be used as a carrier for osteoinductive agents. κ-Carrageenan, a highly hydrophilic and biocompatible seaweed-derived sulfated-polysaccharide, promotes pre-osteoblast activity required for bone regeneration. Whether κ-carrageenan can functionalize OCP-coating to enhance osseointegration of titanium implants is unclear. This study aimed to analyze carrageenan-functionalized biomimetic OCP-coated titanium structure, and effects of carrageenan functionalization on pre-osteoblast behavior and osteogenic differentiation. Titanium discs were coated with OCP/κ-carrageenan at 0.125–2 mg/ml OCP solution, and physicochemical and biological properties were investigated. κ-Carrageenan (2 mg/ml) in the OCP coating of titanium discs decreased the pore size in the sheet-like OCP crystal by 41.32%. None of the κ-carrageenan concentrations tested in the OCP-coating did affect hydrophilicity. However, κ-carrageenan (2 mg/ml) increased (1.26-fold) MC3T3-E1 pre-osteoblast spreading at 1 h i.e., κ-Carrageenan in the OCP-coating increased pre-osteoblast proliferation (max. 1.92-fold at 2 mg/ml, day 1), metabolic activity (max. 1.50-fold at 2 mg/ml, day 3), and alkaline phosphatase protein (max. 4.21-fold at 2 mg/ml, day 3), as well as matrix mineralization (max. 5.45-fold at 2 mg/ml, day 21). κ-Carrageenan (2 mg/ml) in the OCP-coating increased gene expression of Mepe (4.93-fold) at day 14, and Runx2 (2.94-fold), Opn (3.59-fold), Fgf2 (3.47-fold), Ocn (3.88-fold), and Dmp1 (4.59-fold) at day 21 in pre-osteoblasts. In conclusion, κ-carrageenan modified the morphology and microstructure of OCP-coating on titanium discs, and enhanced pre-osteoblast metabolic activity, proliferation, and osteogenic differentiation. This suggests that κ-carrageenan-functionalized OCP coating may be promising for in vivo improvement of titanium implant osseointegration.